Association of Diabetes Self-Care Management with Glycemic Control among Adults with Type 2 Diabetes in Bangladesh - Hossain, Mahmudul; Rahman, Md Mantaka; Dastider , Sathi; Sharmin, Ajmari; Alam, Ummul Khair (Bangladesh Medical Journal, 2026)
Effective self-care is essential for achieving glycemic control, yet adherence remains suboptimal in many low- and middle-income settings, making an understanding of self-management patterns crucial for guiding patient-centered interventions. This study evaluates self-care practices and their relationship with glycemic outcomes among adults with type 2 diabetes mellitus (T2DM) attending tertiary hospitals in Bangladesh. A cross-sectional study of 278 adults with T2DM was conducted at two tertiary hospitals in Dhaka. Data were collected using a structured questionnaire covering socio-demographic characteristics, diabetes history, comorbidities, glycemic records, and the Diabetes Self-Management Questionnaire (DSMQ). Glycemic control was assessed using fasting blood sugar (FBS), 2-hour after breakfast glucose (2-HABF), and glycated hemoglobin (HbA1c). Descriptive statistics, chi-square tests, and Pearson’s correlation coefficients were used, with significance set at p<0.05. The mean age of respondents was 47.9 ± 10.9 years; 71.9% were female, and 65.8% lived in urban areas. Most participants (78.4%) had diabetes for ≤10 years, 63.3% reported a family history, and 90.7% were on pharmacological treatment—mainly oral hypoglycaemic agents (63.5%). Hypertension (42.8%) and hypothyroidism (32%) were the most common comorbidities. Poor glycemic control was widespread: 81.4% had FBS ≥7 mmol/L, 71.6% had 2-HABF ≥10 mmol/L, and 55.3% had HbA1c ≥7%. Only 42.4% demonstrated adequate overall self-care, with the lowest adequacy in glucose monitoring (30.6%) and physical activity (34.7%), and the highest in medication adherence (72.3%) and follow-up visits (62.6%). Higher DSMQ subscale scores showed significant negative correlations with HbA1c (p<0.01), indicating that better self-care was associated with improved glycemic outcomes. Adequate medication adherence, dietary compliance, physical activity, glucose monitoring, and follow-up visits were significantly associated with good glycemic control (p<0.01). Residence and treatment modality were also significant predictors of having available glycemic records (p<0.05). Self-care management practices among Bangladeshi adults with T2DM were suboptimal and strongly associated with poor glycemic control. Enhancing structured diabetes self-management education, improving patient–provider communication, and promoting lifestyle modification are essential for optimizing metabolic outcomes in this population. Bangladesh Med J. 2025 Sept; 54(1): 1-8